2016
DOI: 10.5784/32-1-541
|View full text |Cite
|
Sign up to set email alerts
|

Low volatility sector-based portfolios: a South African case

Abstract: Portfolios and indices that have been specifically constructed to have low risk attributes have received increasing interest in the recent international literature. It has been found that portfolios constructed by targeting low risk assets have predominantly outperformed portfolios constructed to have higher risks. This anomaly has led to renewed interest in constructing low volatility portfolios by practitioners. This study analyses a variety of low volatility portfolio construction methodologies using sector… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 41 publications
1
4
0
Order By: Relevance
“…Contrary to the theoretical expectation, the results suggest a negative relation between risk and return. However, the result is in line with previous findings (see Khuzwayo 2015;Oladele & Bradfield 2016;Panulo 2014).…”
Section: Standard Deviation Quintile Portfolio Analysissupporting
confidence: 93%
See 4 more Smart Citations
“…Contrary to the theoretical expectation, the results suggest a negative relation between risk and return. However, the result is in line with previous findings (see Khuzwayo 2015;Oladele & Bradfield 2016;Panulo 2014).…”
Section: Standard Deviation Quintile Portfolio Analysissupporting
confidence: 93%
“…The results in this study are also consistent with those of Ang et al (2006), who found large negative alphas for US shares with high idiosyncratic volatility. The results could also explain the outperformance of the various low-volatility trading strategies investigated by Khuzwayo (2015), Panulo (2014) and Oladele and Bradfield (2016).…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations